Neoadjuvant (induction) chemotherapy in advanced bladder carcinoma - (:unkn) unknown (My University, 1993)
Traditional approaches for the treatment of locally advanced bladder tumours may not be sufficient enough. Neoadjuvant chemotherapy, a new modality, may be beneficial by enhancing the local and systemic control of the disease. The background of this new modality and early results of various trials are discussed.
Keywords: Humans; Urinary Bladder Neoplasms; Doxorubicin; Methotrexate; Survival Rate; Antineoplastic Combined Chemotherapy Protocols; Vinblastine; Cyclophosphamide; Chemotherapy, Adjuvant; Organoplatinum Compounds